The Lived experience of heart disease : a woman's perspective - Woulf, Amanda L. (My University, 2011)
Every minute a woman in the United States dies from cardiovascular disease (Weiss, 2009). Despite the prevalence of heart disease, women continue to underestimate the threat of heart disease. The diagnosis of heart disease can mean battling with uncertainties of what the future will hold. Further examination of the lived experiences of women with heart disease is needed to identify the uncertainties experienced by women that impact their health behaviors. The purpose of this descriptive, phenomenological study was to examine and describe the lived experience of heart disease from the perspectives of women. Mishel's Uncertainty in Illness Theory (1988, 1990)served as the theoretical foundation for this study. Mishel's theory was developed as a guide in understanding how individuals cognitively develop meaning to their illness events. Data were collected from a purposive sample of women with heart disease. Data were collected through unstructured, face-to-face, audio-taped interviews. After data were collected and transcribed, it was analyzed using Giorgi's phenomenological method. Data were then described, compared, and applied to Mishel's Uncertainty in Illness Theory. Results, implications, and conclusions were then based on the data received.
A Clinical Paper submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing-Family Nurse Practitioner
Keywords: Cardiovascular system - Diseases; Heart - Diseases; Women - Health and hygiene; Heart disease in women